Penerapan Akuntansi ISAK 35 Terhadap Akuntabilitas Keuangan Masjid (studi kasus masjid besar al-hidayah sagaranten) - Mawardah, Salwa Manik (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2022)
This research conducts to find out the compatibility of financial statements based on ISAK NO.35 and how the bookkeeping records of Great Mosque Al-Hidayah based on general accounting principles. In collecting the data in the research that occurred in Great Mosque Al-Hidayah Sagaranten, the researcher did interview and documentation. In analyzing the data, the researcher used descriptive qualitative method, it described the data according to what is found in the financial statements and compared with the theory that is relevan to the problems, then drew the conclusion. According to the research, it can be concluded that the financial statements of Great Mosque Al-Hidayah Sagaranten is not in accordance with ISAK 35 and still in the simple cash form. It’s financial statements just contain financial position, while comprehensive income statements, changes in net assets reports, cash flow reports and notes to financial statements are excluded. Keywords : ISAK 35, Mosque, Non-profit